A three-dimensional view of structural changes caused by deactivation of fluid catalytic cracking catalysts - J. Ihli (Nature Portfolio, 2017)
Catalyst deactivation in fluid catalytic cracking processes is unavoidably associated with structural changes. Here, the authors visualize the deactivation of zeolite catalysts by ptychography and other imaging techniques, showing pronounced amorphization of the outer layer of the catalyst particles.